Tafazzin deficiency causes substantial remodeling in the lipidome of a mouse model of Barth Syndrome cardiomyopathy - Hachmann, Malte; Gülcan, Güntas; Rajendran, Ranjithkumar; Höring, Marcus; Liebisch, Gerhard; Bachhuka, Akash; Kohlhaas, Michael; Maack, Christoph; Ergün, Süleyman; Dudek, Jan; Karnati, Srikanth (Frontiers in Molecular Medicine, 2024)
Barth Syndrome (BTHS) is a rare X-linked disease, characterized clinically by cardiomyopathy, skeletal myopathy, neutropenia, and growth retardation. BTHS is caused by mutations in the phospholipid acyltransferase tafazzin (Gene: TAFAZZIN, TAZ). Tafazzin catalyzes the final step in the remodeling of cardiolipin (CL), a glycerophospholipid located in the inner mitochondrial membrane. As the phospholipid composition strongly determines membrane properties, correct biosynthesis of CL and other membrane lipids is essential for mitochondrial function. Mitochondria provide 95% of the energy demand in the heart, particularly due to their role in fatty acid oxidation. Alterations in lipid homeostasis in BTHS have an impact on mitochondrial membrane proteins and thereby contribute to cardiomyopathy. We analyzed a transgenic TAFAZZIN-knockdown (TAZ-KD) BTHS mouse model and determined the distribution of 193 individual lipid species in TAZ-KD and WT hearts at 10 and 50 weeks of age, using electrospray ionization tandem mass spectrometry (ESI-MS/MS). Our results revealed significant lipid composition differences between the TAZ-KD and WT groups, indicating genotype-dependent alterations in most analyzed lipid species. Significant changes in the myocardial lipidome were identified in both young animals without cardiomyopathy and older animals with heart failure. Notable alterations were found in phosphatidylcholine (PC), phosphatidylethanolamine (PE), lysophosphatidylethanolamine (LPE), lysophosphatidylcholine (LPC) and plasmalogen species. PC species with 2–4 double bonds were significantly increased, while polyunsaturated PC species showed a significant decrease in TAZ-KD mice. Furthermore, Linoleic acid (LA, 18:2) containing PC and PE species, as well as arachidonic acid (AA, 20:4) containing PE 38:4 species are increased in TAZ-KD. We found higher levels of AA containing LPE and PE-based plasmalogens (PE P-). Furthermore, we are the first to show significant changes in sphingomyelin (SM) and ceramide (Cer) lipid species Very long-chained SM species are accumulating in TAZ-KD hearts, whereas long-chained Cer and several hexosyl ceramides (HexCer) species accumulate only in 50-week-old TAZ-KD hearts These findings offer potential avenues for the diagnosis and treatment of BTHS, presenting new possibilities for therapeutic approaches.